Skin in vitro models to study dermal white adipose tissue role in skin healing - Lago, M. E. L. (2018)
The perception of the role of adipose tissue has been changing over the years. For a long time, it was simply seen as an energy storage organ that confers mechanical protection and heat insulation. However, an increasing number of studies demonstrate the complex role of adipose tissue in the systemic regulation of processes such as immunity and inflammation. Therefore, adipose tissue is currently considered a metabolic organ with varied features and potential action in different physio and pathological processes. In the particular case of the skin adipose depot, dermal white adipose tissue has been recently described as a contributor to a wide range of events including hair formation and cycle and cutaneous wound healing. This chapter aims to provide an overview of the role of adipose tissue and their components in skin homeostasis. Furthermore, a review on the approaches that have been followed to study these processes, not only in vitro but also in vivo, will be provided. Ultimately, adipose tissue engineering is presented as a valuable strategy to generate enhanced in vitro models in which the role of adipose tissue can be further unraveled.